Migrasi dan Tata Ruang : Dinamika Mobilitas Penduduk dalam Transformasi Wilayah di Provinsi Gorontalo - Mohamad Zainudin Usman; Fitriyane Lihawa; Iswan Dunggio (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to analyze the dynamics of population mobility in Gorontalo Province, focusing on migration patterns, driving factors, and their impacts on regional development. The research employs a descriptive quantitative approach based on secondary data from Long Form Sensus Penduduk 2020 and official publications from Badan Pusat Statistik. The findings reveal that Gorontalo City serves as the primary destination for in-migration, while Gorontalo Regency is the main source of out-migration. Economic motives dominate migration drivers, followed by educational and socio-familial factors. Migration contributes to economic growth in destination areas but also presents challenges such as infrastructure disparity and pressure on public services, especially in origin and emerging regions like Boalemo and Pohuwato. These findings highlight the importance of development planning that is responsive to population mobility dynamics to achieve inclusive and sustainable growth.